Plasma glycocholic acid and linoleic acid identified as potential mediators of mitochondrial bioenergetics in Alzheimer’s dementia - Amick, K. Allison; Mahapatra, Gargi; Gao, Zhengrong; Dewitt, Amber; Craft, Suzanne; Jain, Mohit; Molina, Anthony J. A. (Frontiers in Aging Neuroscience, 2022)
Mitochondrial bioenergetic alterations occur in the brain and peripheral cells of patients with Alzheimer’s disease (AD). This study focuses on plasma circulating factors, namely lipids, as mediators of systemic bioenergetic differences in participants with normal cognition (NC), mild cognitive impairment (MCI), and dementia due to probable AD (DEM). We examined bioenergetic differences across cognitive groups by measuring the mitochondrial respiration of peripheral blood mononuclear cells (PBMCs) from 37 participants (12 NC, 12 MCI, 13 DEM). PBMC bioenergetics were lower in the DEM group compared to the NC group. To determine whether circulating factors can mediate bioenergetic differences according to cognitive status, we exposed naïve neuronal Neuro-2a (N2a) cells to plasma from each participant in-vitro. N2a bioenergetics were lower following plasma exposure from DEM compared to NC group participants. Notably, PBMC Max and N2a Max positively correlated, suggesting that circulating factors modulate the bioenergetics of naïve N2a cells according to the bioenergetic capacity of donor primary PBMCs. To identify lipid metabolites that may contribute to bioenergetic differences between cognitive groups, we performed liquid chromatography-mass spectrometry to assess the abundance of individual lipid species and correlated PBMC and N2a bioenergetics. Glycocholic acid (GCA) positively correlated with PBMC and N2a bioenergetics, while linoleic acid (LA) was negatively correlated. These data suggest that GCA and LA may contribute to the stimulatory and inhibitory bioenergetics effects related to cognitive status. Post-hoc analyses revealed that GCA abundance was lower by 52.9% in the DEM group compared to the NC group and that LA abundance was higher by 55.7% in the DEM group compared to the NC group. To validate these findings, we examined the abundance of GCA and LA in the larger, more diverse, parent cohort (n = 378) and found similar results; GCA abundance was lower by 29.7% in the DEM group compared to the NC group and LA abundance was higher by 17.8% in the DEM group compared to the NC group. These data demonstrate that circulating factors have a direct effect on mitochondrial bioenergetics and that individual circulating factors identified to be associated with mitochondrial function are differentially expressed in patients with dementia.